PEMANFAATAN ALAT FILTRASI UNTUK PEMENUHAN KEBUTUHAN AIR BERSIH WARGA DUSUN GONDANG DONOKERTO KECAMATAN TURI KABUPATEN SLEMAN - Marausna, Gaguk; Prasetiyo, Erwan Eko; Putra, Ikbal Rizki; Sehono; Setiawan, Hery; Yudhono, Reo; Errisonia, Arfie Armelia; Widyanto, Dwi (Jurnal Berdaya Mandiri, 2025)
Gondang Hamlet, Donokerto Village, faces challenges in accessing clean water, especially during the dry season, as the main water source comes from a turbid river flow. This community service initiative aims to address the issue by implementing a simple water filtration technology using a combination of media such as silica sand, zeolite, activated carbon, and magnesium. The design, training, and installation processes were carried out collaboratively with local residents to ensure sustainable usage. The results showed an improvement in water quality after filtration, although there was a challenge in the form of reduced water flow, which was resolved by installing an additional pump. This program also emphasizes the involvement of the community in maintaining the equipment and conducting regular monitoring to ensure the long-term functionality of the system. Keywords: clean water, filtration device, community service, zeolite, activated carbon